Learning Adobe After Effects CC - Sengstack, Jeff (InfiniteSkills, 2013)
"In this Adobe After Effects CC training course, expert author Jeff Sengstack teaches you how to get the most out your post-production effects and compositing with this powerful software from Adobe. Designed for the beginner, you will learn how to use After Effects CC from the ground up, no previous experience is necessary! Once you have completed this Adobe After Effects CC video tutorial, you will have a solid grasp on how to apply the tools in this visual effects software to your own video projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.